Observation Results related to Problems and Implementation of Early Childhood Mathematics Learning at RA Babussalam - Dhiya Farah Azizah (Tajdid Al-Athfal, 2022)
This research is motivated by early childhood mathematics learning which is not yet effective and ideal. especially in group A RA Babussalam. Therefore, an effective ideal mathematics learning is needed. This research method is done by means of observation, data collection techniques in this study using observation, interviews, and documentation. The results showed that the problems that arise in learning mathematics for children in group A in RA Babussalam are not all children dare or are still shy to talk to the teacher when the teacher asks questions to children during mathematics learning and teachers play a more active role in learning mathematics. keywords : Implementation of Children's Mathematics Learning, Educational Game Tool, Assesment of Children's Mathematics Learning